2010
DOI: 10.1177/0003319710366702
|View full text |Cite
|
Sign up to set email alerts
|

Association of Reduced Zinc Status With Angiographically Severe Coronary Atherosclerosis: A Pilot Study

Abstract: In vitro studies attribute antiatherogenic and insulin-like properties to zinc (Zn). However, only a few conflicting clinical data exist concerning the relationship between Zn and coronary artery disease (CAD) as well as glycemic indices. We studied 72 patients without prior history of myocardial infarction or revascularization procedures, who underwent coronary angiography for evaluation of chest pain. Coronary artery disease severity was estimated using 3 angiographic scores. Zn in serum and 24-hour urine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…Patients with AMI showed significant decrease in serum zinc level than patients with UA and those who received reperfusion therapy (p= 0.033 and 0.002, respectively). These results were in agreement with the study of Giannoglou et al 2010 andCebi et al 2011 showed that serum Zn was not significantly associated with CHD risk and severity (P = 0.320). [45][46] In contrast, a study of Islamoglu et al 2011 found that serum Zn was significantly lower in patients than in healthy control (P < 0.010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with AMI showed significant decrease in serum zinc level than patients with UA and those who received reperfusion therapy (p= 0.033 and 0.002, respectively). These results were in agreement with the study of Giannoglou et al 2010 andCebi et al 2011 showed that serum Zn was not significantly associated with CHD risk and severity (P = 0.320). [45][46] In contrast, a study of Islamoglu et al 2011 found that serum Zn was significantly lower in patients than in healthy control (P < 0.010).…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with the study of Giannoglou et al 2010 andCebi et al 2011 showed that serum Zn was not significantly associated with CHD risk and severity (P = 0.320). [45][46] In contrast, a study of Islamoglu et al 2011 found that serum Zn was significantly lower in patients than in healthy control (P < 0.010). 47 Moreover, in the study of Bayir et al 2013, serum Zn concentration was significantly less in the CHD group compared to the control group (p< 0.010).…”
Section: Discussionsupporting
confidence: 92%
“…Such lack of association between zinc intake/plasma concentration and cardiovascular disease was similarly reported in younger adults [17] , [18] and in the prospective Physicians' Health Study II [19] . In this latter study, the same incidence of cardiovascular events was found in individuals aged 50 years or older that were randomized to nutritional supplementation with the daily-recommended dose of zinc (11 mg/day) or placebo during 11.2 years.…”
Section: Discussionsupporting
confidence: 58%
“…Low serum zinc/24-hour urine zinc ratio is associated with angiographically severe atherosclerosis. It was observed that low zinc levels were associated with patients with cardiovascular diseases (1,6).…”
Section: Discussionmentioning
confidence: 99%